Drug Inventory Control As A Method Of Teaching Health Economics -A Six Stage Lecture Discussion - Soudarssanane M.B (Wolters Kluwer Medknow Publications, 1997)
Research question: Can drug inventory control be used as a method of teaching health economics to undergraduate medical students? Objectives: 1. To use drug inventory control method for highlighting the concept of cost â€" analysis with cost â€" effectiveness and 2. Preparing a list of the type and quantity of essential drugs at the health center level given the morbidity pattern and population data. Study design: Lecture- discussion. Setting: Health centre. Participants: 4 batches of final year MBBS students. Study variables: Drug inventory at health centre level, cost of individual items, cost â€" effectiveness of storing individual items. Outcome variables: ABC and VED analysis of items required at health centre level. Observations: The students appreciated that in addition to the information on expenditure, the implication of ABC analysis was to identify â€˜fast movingâ€ and â€˜slow movingâ€ drug items. They also observed that the process might be useful in limiting the number and quality of drugs. Regarding VED analysis, they understood its necessity for information on the nature of drugs that were to be maintained in the stock at any given point of time, which in turn would make it possible to screen out unwanted items and the saving might be utilized in procuring useful and scientific drug combinations. The topic of Health Economics was taught to four batches of medical students at JIPMER (as part of the overall topic of Health Management). Data from an actual study of Drug Inventory Control in the Health Centers of JIPMER, using the ABC and VED techniques, was used in the lecture discussion. Individual handouts of the findings of the study were provided to the students of facilitate the discussion. The Drug Inventory Control Method was used to highlight the concepts of cost analysis, cost- effectiveness and the possibility of preparing a list of the type and quantity of essential drugs at the Health Centre level given the morbidity pattern and population data. Evaluation of the lecture discussion was done using pre and post tests and general feedback from the students. Details of the discussion, procedures and suggestions by the students are presented.